Battery
By forming a passivation layer on the surface of the stainless steel layer of the lithium -ion battery, the problem of corrosion and electrolyte decomposition caused by the contact between the electrolyte and the stainless steel layer is solved, and the cycle stability and electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN202411291387.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-14
AI Technical Summary
In lithium-ion batteries, the contact between the electrolyte and the stainless steel layer leads to corrosion and the electrolyte decomposition, resulting in a degradation of the battery performance.
Add the compound shown in formula 1 to the surface of the stainless steel layer of the battery component to form a passivation layer to avoid direct contact between the electrolyte and the stainless steel layer.
Effectively suppress the corrosion of the stainless steel layer and the decomposition of the electrolyte, and improve the cycle stability and electrochemical properties of the battery.
Smart Images

Figure CN118801058B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a battery. Background Art
[0002] Lithium-ion batteries have been widely promoted and applied due to their high energy density, long cycle life, high safety, etc. According to the packaging type, lithium-ion batteries can be divided into soft-pack batteries, square aluminum shell batteries and cylindrical batteries.
[0003] Taking cylindrical batteries as an example, cylindrical batteries have higher volume energy density and mature manufacturing processes, and are given priority for use in passenger car power batteries. However, as people's requirements for battery energy density and charging speed continue to increase, the size of cylindrical batteries continues to increase, and the number of tabs continues to increase, resulting in an increase in the welding area between the tabs and the battery shell (such as the negative pole). Welding will damage the coating on the surface of stainless steel materials. When the electrolyte comes into contact with these parts, it is easy to cause corrosion at the battery welding points and the electrolyte is continuously consumed and decomposed, resulting in a decrease in battery performance. Summary of the invention
[0004] The present invention aims to solve, at least to some extent, the technical problem that some battery components in contact with an electrolyte may react with the electrolyte. To this end, one object of the present invention is to provide a battery. A passivation layer is formed on a stainless steel layer at the contact surface of the battery component and the electrolyte by using the compound shown in Formula 1 to effectively prevent the reaction from occurring.
[0005] The first aspect of the present invention provides a battery. According to an embodiment of the present invention, the battery includes: an electrolyte, a battery component in contact with the electrolyte; at least the contact surface of the battery component with the electrolyte includes a stainless steel layer, and the electrolyte includes at least a compound shown in Formula 1, and the compound shown in Formula 1 is:
[0006]
[0007] wherein m is an integer of 0 to 3, n is an integer of 0 to 3, and m and n are not both 0, p is an integer of 1 to 5, R0 is a single bond or a methylene group, R1 is hydrogen, halogen, a hydrocarbon group having 1 to 5 carbon atoms, or a halogenated hydrocarbon group having 1 to 5 carbon atoms, and R2, R3, and R4 are independently , , , , , or .
[0008] The present invention uses the compound shown in Formula 1 to form a passivation layer on the surface of the stainless steel layer, which can effectively avoid direct contact between the electrolyte and the stainless steel layer, which is beneficial to inhibiting the corrosion of the stainless steel layer and preventing the electrolyte from being continuously decomposed, so that the battery has better cycle stability.
[0009] According to an embodiment of the present invention, the above battery may further include at least one of the following additional technical features:
[0010] In some embodiments, the compound represented by Formula 1 is selected from:
[0011]
[0012] At least one of .
[0013] In some embodiments, in the electrolyte, the mass proportion of the compound represented by Formula 1 is 0.02% to 10%.
[0014] In some embodiments, the battery includes a shell and / or a cover plate, and also includes a negative electrode current collector. The battery component includes a portion on the shell and / or the cover plate that is welded to the negative electrode current collector, and the portion includes a stainless steel layer.
[0015] In some embodiments, the cross-sectional area of the portion of the housing and / or cover plate that is welded to the negative electrode current collector is 5 mm 2 ~400 mm 2 .
[0016] In some embodiments, the battery comprises a cylindrical battery.
[0017] In some embodiments, the outer diameter of the cylindrical battery shell is 20 mm to 65 mm.
[0018] In some embodiments, the electrolyte satisfies any one of the following (1) to (3):
[0019] (1) The electrolyte contains a solvent, and the solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether compound solvent, a phosphorus compound solvent, a sulfur compound solvent, and an aromatic fluorine compound solvent;
[0020] (2) The electrolyte contains a conductive salt, and the conductive salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide, sodium hexafluorophosphate (NaPF6), sodium bis(fluorosulfonyl)imide (NaFSI) and sodium bis(trifluoromethylsulfonyl)imide;
[0021] (3) The electrolyte contains an additive, and the additive includes at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC) and succinic anhydride (SA).
[0022] In some embodiments, the battery further comprises a positive electrode material, wherein the positive electrode active material comprises lithium iron phosphate, lithium cobalt oxide, a ternary material LiNi x Co y Mn z O2, lithium iron manganese phosphate materials, lithium-rich manganese-based materials xLi2MnO3·(1-x)LiMO2, lithium nickel manganese oxide, lithium manganese oxide, sodium iron phosphate materials, three-dimensional tunnel-type Na 0.44 At least one of MnO2, P2 layered NaMO2, NaFePO4, Na4Fe3(PO4)2P2O7, Na3V2(PO4)3, Na3V2(PO4)2F3, Na2Fe(CN)6 and Na2MnFe(CN)6.
[0023] In some embodiments, the battery further comprises a negative electrode material, the negative electrode material comprising at least one of graphite, hard carbon, a silicon-containing compound and silicon.
[0024] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0025] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0026] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0029] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0030] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0031] A first aspect of an embodiment of the present invention provides a battery, comprising an electrolyte and a battery component in contact with the electrolyte; at least the contact surface of the battery component with the electrolyte comprises a stainless steel layer, and the electrolyte comprises at least a compound represented by Formula 1, wherein the compound represented by Formula 1 is:
[0032]
[0033] wherein m is an integer of 0 to 3, n is an integer of 0 to 3, and m and n are not both 0, p is an integer of 1 to 5, R0 is a single bond or a methylene group, R1 is hydrogen, halogen, a hydrocarbon group having 1 to 5 carbon atoms, or a halogenated hydrocarbon group having 1 to 5 carbon atoms, and R2, R3, and R4 are independently , , , , , or .
[0034] Some parts of some batteries (such as cylindrical batteries) (such as shells and / or covers) are made of stainless steel. Usually, the surface of these parts will have a nickel plating layer to protect the stainless steel layer and effectively prevent it from coming into contact with the electrolyte and reacting. However, when the nickel plating on the surface of the stainless steel layer of the battery parts in contact with the electrolyte is damaged, the stainless steel layer is directly exposed to the electrolyte. When the battery is charged and discharged, the electrolyte will corrode the stainless steel layer and cause severe corrosion. At the same time, the electrolyte is decomposed in large quantities, resulting in poor battery cycle stability.
[0035] The compound shown in Formula 1 used in the embodiment of the present invention can form a passivation layer on the surface of the stainless steel layer, which can effectively avoid direct contact between the electrolyte and the stainless steel layer, which is beneficial to inhibiting corrosion of the stainless steel layer and preventing the electrolyte from being continuously decomposed, so that the battery has better cycle stability.
[0036] In the embodiment of the present invention, the compound shown in Formula 1 has a strong electronegativity, has a strong binding energy with the stainless steel layer, is adsorbed on the surface of the stainless steel, and promotes the formation of a passivation layer; the compound shown in Formula 1 can form a passivation layer with a network structure on the surface of the stainless steel layer, and the passivation layer has high density, which can effectively avoid direct contact between other components of the electrolyte and the stainless steel layer, which is beneficial to inhibiting the corrosion of the stainless steel layer, and at the same time, the electrolyte is prevented from being continuously decomposed, so that the battery provided by the embodiment of the present invention has good cycle stability; in addition, the passivation layer with a three-dimensional network structure formed by the compound shown in Formula 1 has high stability, which can be suitable for protecting a continuous interface and a stainless steel surface with a large interface.
[0037] In an embodiment of the present invention, the compound represented by Formula 1 can be directly added to an electrolyte, and the electrolyte can be injected into a battery. During the battery formation process or the battery operation process, the compound represented by Formula 1 reacts on a possible stainless steel surface layer to form a passivation layer as a protective layer, and the elements in the passivation layer include sulfur.
[0038] In some embodiments, the compound represented by Formula 1 is selected from:
[0039]
[0040] At least one of .
[0041] In some embodiments, in the electrolyte, the mass proportion of the compound represented by Formula 1 is 0.02% to 10%. In specific examples, the mass proportion of the compound represented by Formula 1 is 0.02%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0042] In the embodiment of the present invention, the mass proportion of the compound represented by Formula 1 in the electrolyte is 0.02% to 10%, which is the content of the compound represented by Formula 1 in the initial state of the electrolyte, and at this time, it has not been used to form a passivation layer. This addition amount is conducive to forming a passivation layer of effective thickness on the surface of the stainless steel, preventing the electrolyte components from being decomposed and thus deteriorating the cycle performance; on the other hand, it is conducive to ensuring that the electrolyte maintains a high conductivity.
[0043] In some embodiments, the battery includes a shell and / or a cover plate, and also includes a negative electrode current collector. The battery component includes a portion on the shell and / or the cover plate that is welded to the negative electrode current collector, and the portion includes a stainless steel layer.
[0044] In the embodiment of the present invention, the shell and / or cover of the battery are made of stainless steel, and there will be a nickel-plated layer on the surface of the stainless steel. However, when the shell and / or cover of the battery are welded to the negative electrode current collector by welding, the nickel-plated layer on the surface of the stainless steel will be destroyed and then integrated with the negative electrode current collector to form a welding point. The welding point position is directly in contact with the electrolyte due to the lack of nickel-plated layer protection, which makes it easy for the shell and / or cover to be corroded by the electrolyte and consume a large amount of electrolyte, resulting in poor cycle stability. In the embodiment of the present invention, the compound shown in Formula 1 forms a passivation layer at the welding connection part, which can effectively prevent the welding connection part from continuing to contact with the electrolyte, prevent the welding part from being corroded by the electrolyte, and avoid the electrolyte from being consumed in large quantities, which is beneficial to improving the electrochemical performance of the battery.
[0045] In addition, the portion of the shell and / or cover plate that is welded to the negative electrode current collector has a larger current density and a lower potential, which can further promote the reduction of the compound represented by Formula 1 to form a passivation coating with a network structure.
[0046] Furthermore, the welding method adopted by the welding connection is laser welding.
[0047] In the embodiment of the present invention, the negative electrode current collector is connected to the battery shell and / or cover plate by laser welding. This welding method causes significant damage to the nickel-plated layer on the surface of the stainless steel layer.
[0048] In some embodiments, the cross-sectional area of the portion of the housing and / or cover plate where the negative electrode current collector is welded is 5 mm 2 ~400 mm 2 In a specific example, the cross-sectional area of the portion of the shell and / or cover plate where the negative electrode current collector is welded is 5 mm 2 , 10 mm 2 , 50 mm 2 , 100 mm 2 , 150 mm 2 , 200 mm 2 , 250 mm 2 , 300 mm 2 、350mm 2 or 400 mm 2 wait.
[0049] In the embodiment of the present invention, the cross-sectional area of the welded connection portion affects the amount of the compound shown in Formula 1 and the electrochemical performance of the battery. The larger the cross-sectional area of the welded connection portion, the larger the amount of the compound shown in Formula 1 required. In particular, when the passivation layer is formed by adding the compound shown in Formula 1 to the electrolyte, the cross-sectional area of the welded connection portion in the embodiment of the present invention is 5 mm 2 ~400 mm 2Adding an appropriate amount of the compound shown in Formula 1 into the electrolyte can form a passivation layer that fully covers the cross-sectional position without increasing the ionic conductivity of the electrolyte, thereby ensuring that the battery has higher electrochemical performance.
[0050] Furthermore, the cross-sectional area of the portion of the shell and / or cover plate that is welded to the negative electrode current collector is 30 mm 2 ~300 mm 2 In a specific example, the cross-sectional area of the portion of the shell and / or cover plate that is welded to the negative electrode current collector is 30 mm 2 , 60 mm 2 , 90 mm 2 , 120 mm 2 , 160 mm 2 , 190 mm 2 , 210 mm 2 , 240 mm 2 , 270 mm 2 or 300 mm 2 wait.
[0051] The embodiment of the present invention provides that the cross-sectional area of the portion where the negative electrode current collector is welded to the shell and / or cover is 30 mm 2 ~300 mm 2 , which is conducive to further obtaining batteries with higher electrochemical performance.
[0052] In some embodiments, the battery comprises a cylindrical battery.
[0053] Cylindrical batteries have higher volume energy density and mature manufacturing processes, and are given priority for use in passenger car power batteries. However, as people's requirements for battery energy density and charging speed continue to increase, the size of cylindrical batteries continues to increase, and the number of tabs continues to increase, resulting in an increase in the welding area between the tabs and the battery shell (such as the negative pole). When the electrolyte comes into contact with these parts, it is easy to cause corrosion at the battery welding points and the electrolyte is continuously consumed and decomposed, causing the battery performance to deteriorate. Therefore, the cylindrical battery provided in the embodiment of the present invention has more practical application value.
[0054] In some embodiments, the outer diameter of the cylindrical battery shell is 20 mm to 65 mm. In a specific example, the outer diameter of the cylindrical battery shell is 20 mm, 25 mm, 30 mm, 32 mm, 34 mm, 36 mm, 38 mm, 40 mm, 42 mm, 44 mm, 46 mm, 48 mm, 50 mm, 55 mm, 60 mm or 65 mm, etc.
[0055] The cylindrical battery provided in the embodiment of the present invention has a shell outer diameter of 30 mm to 55 mm, which can ensure a high energy density while having a low discharge temperature rise of the battery, and will not increase the difficulty of battery PACK (Package).
[0056] In some embodiments, the battery further includes a roll core, the roll core including a positive electrode sheet, a negative electrode sheet, and a separator.
[0057] Furthermore, the negative electrode sheet includes a negative electrode active material layer and a negative electrode current collector, and the negative electrode active material layer covers one side or both sides of the negative electrode current collector.
[0058] Further, the negative electrode active material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductor.
[0059] Furthermore, the mass ratio of each component in the negative electrode active material layer is: 90% to 99% of the negative electrode active material, 0% to 5% of the negative electrode conductive agent and 1% to 10% of the negative electrode binder.
[0060] Furthermore, the negative electrode active material includes at least one of graphite, hard carbon, a silicon-containing compound, and silicon.
[0061] Furthermore, the negative electrode binder includes at least one of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol and sodium polyacrylate.
[0062] Furthermore, the negative electrode conductive agent includes at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber and graphene.
[0063] Furthermore, the negative electrode current collector includes at least one of copper foil, composite copper foil, foam nickel, foam copper and aluminum foil.
[0064] Furthermore, the positive electrode sheet includes a positive electrode active material layer and a positive electrode current collector, and the positive electrode active material layer covers one side or both sides of the positive electrode current collector.
[0065] Further, the positive electrode active material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductor.
[0066] Furthermore, the mass ratio content of each component in the positive electrode active material layer is: 90% to 99.5% of the positive electrode active material, 0.25% to 5% of the positive electrode conductor and 0.25% to 5% of the positive electrode binder.
[0067] Furthermore, the positive electrode active materials include lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), ternary materials (LiNi x Co y Mn z O2 (x+y+z=1)), lithium iron manganese phosphate materials, lithium-rich manganese-based materials (xLi2MnO3·(1-x)LiMO2), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), lithium manganese oxide (LiMn2O4), sodium iron phosphate materials, three-dimensional tunnel type Na 0.44 At least one of MnO2, P2 layered NaMO2 (M is one, two or three of Ni, Mn, Fe), NaFePO4, Na4Fe3(PO4)2P2O7, Na3V2(PO4)3, Na3V2(PO4)2F3, Na2Fe(CN)6 and Na2MnFe(CN)6.
[0068] Furthermore, the positive electrode binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride (PVDF), polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone and polyurethane.
[0069] Furthermore, the positive electrode conductive agent includes at least one of carbon black, acetylene black, graphene, Ketjen black and carbon fiber.
[0070] Furthermore, the positive electrode current collector includes at least one of aluminum foil, composite aluminum foil and nickel foil.
[0071] Furthermore, the material of the diaphragm is not limited, and those skilled in the art can select it according to actual needs. Furthermore, in an embodiment of the present invention, the diaphragm material includes at least one of a coated or uncoated polypropylene (PP) diaphragm, a polyethylene (PE) diaphragm, and a polyvinylidene fluoride diaphragm.
[0072] In some embodiments, the electrolyte satisfies any one of the following (1) to (3):
[0073] (1) The electrolyte contains a solvent, and the solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether compound solvent, a phosphorus compound solvent, a sulfur compound solvent, and an aromatic fluorine compound solvent;
[0074] (2) The electrolyte contains a conductive salt, and the conductive salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide, sodium hexafluorophosphate (NaPF6), sodium bis(fluorosulfonyl)imide (NaFSI) and sodium bis(trifluoromethylsulfonyl)imide;
[0075] (3) The electrolyte contains an additive, and the additive includes at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC) and succinic anhydride (SA).
[0076] In some embodiments, the solvent in the electrolyte includes at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), propyl butyrate (PB), ethyl butyrate (EB), propyl propionate (PP), ethyl propionate (EP), methyl propionate (MP), propyl acetate (PA), fluorobenzene (FB), ethyl acetate (EA), methyl acetate (MA), propyl formate (PF), ethyl formate (EF), methyl formate (MF) and γ-butyrolactone.
[0077] In some embodiments, the conductive salt in the electrolyte accounts for 10% to 20% of the total mass of the electrolyte.
[0078] In the embodiment of the present invention, the conductive salt in the electrolyte accounts for 10% to 20% of the total mass of the electrolyte, which is beneficial to further improve the electrochemical performance of the battery to achieve higher conductivity and chemical stability.
[0079] The second aspect of the present invention provides a method for manufacturing the above-mentioned battery, comprising: adding the compound shown in Formula 1 to the electrolyte; after the electrolyte contacts the surface of the stainless steel, the compound shown in Formula 1 forms a passivation layer on the surface of the stainless steel.
[0080] In the embodiment of the present invention, by directly adding the compound shown in Formula 1 into the electrolyte, it is beneficial to simplify the manufacturing process of the battery, reduce the difficulty of operation, and save costs.
[0081] In some embodiments, in the electrolyte, the mass proportion of the compound represented by Formula 1 is 0.02% to 10%. In specific examples, the mass proportion of the compound represented by Formula 1 is 0.02%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0082] In the embodiment of the present invention, the mass proportion of the compound represented by Formula 1 in the electrolyte is 0.02% to 10%, which is the content of the compound represented by Formula 1 in the initial state of the electrolyte, and at this time, it has not been used to form a passivation layer. This addition amount is conducive to forming a passivation layer of effective thickness on the surface of the stainless steel, preventing the electrolyte components from being decomposed and thus deteriorating the cycle performance; on the other hand, it is conducive to ensuring that the electrolyte maintains a high conductivity.
[0083] In some embodiments, the conditions for the compound shown in Formula 1 to form a passivation layer include: the temperature is the temperature required for battery formation. The specific temperature can be selected based on actual conditions. In a specific example, the conditions for the compound shown in Formula 1 to polymerize to form a passivation layer include: the temperature is 20°C to 60°C; more specifically, the temperature is 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, etc.
[0084] In some embodiments, the conditions for polymerizing the compound represented by Formula 1 to form a passivation layer include: a temperature of 20°C to 45°C; in specific examples, the temperature is 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, 42°C, 44°C or 45°C, etc.
[0085] In the embodiment of the present application, the conditions for the polymerization of the compound represented by Formula 1 to form a passivation layer meet the above-mentioned temperature conditions, and the viscosity of the electrolyte is relatively small, which is conducive to the rapid polymerization of the compound to form a passivation layer with higher density; at the same time, the above-mentioned temperature conditions are met to avoid thermal shrinkage of the battery cell diaphragm, which affects the battery performance.
[0086] In some embodiments, the compound represented by Formula 1 is polymerized to form a passivation layer when the battery is charged for the first time, or forms a passivation layer during the operation of the battery.
[0087] A third aspect of the embodiments of the present invention provides an electrical device, including the above-mentioned battery, or a battery manufactured by the above-mentioned manufacturing method.
[0088] The battery provided by the embodiment of the present invention forms a passivation layer on the surface of the stainless steel layer of the battery component in contact with the electrolyte, thereby preventing the battery component from being corroded by the electrolyte and avoiding a large amount of electrolyte consumption, which is conducive to obtaining a battery with higher electrochemical performance.
[0089] In specific examples, electrical equipment includes 3C digital products, household appliances, passenger cars, drones or electric aircraft, etc.
[0090] The fourth aspect of the embodiment of the present invention provides a new use of the compound shown in Formula 1, which is used to form a passivation layer on the surface of a stainless steel layer to prevent the battery component in contact with the electrolyte from reacting with the electrolyte; at least the contact surface of the battery component in contact with the electrolyte includes a stainless steel layer; the compound shown in Formula 1 is:
[0091]
[0092] wherein m is an integer of 0 to 3, n is an integer of 0 to 3, and m and n are not both 0, p is an integer of 1 to 5, R0 is a single bond or a methylene group, R1 is hydrogen, halogen, a hydrocarbon group having 1 to 5 carbon atoms, or a halogenated hydrocarbon group having 1 to 5 carbon atoms, and R2, R3, and R4 are independently , , , , , or .
[0093] Some battery components (such as the housing and / or cover) are made of stainless steel. Usually, these components have a nickel-plated layer on the surface to protect the stainless steel layer and effectively prevent it from coming into contact with the electrolyte and reacting. However, when the nickel-plated layer on the surface of the stainless steel layer of the battery component in contact with the electrolyte is damaged, the stainless steel layer is directly exposed to the electrolyte. When the battery is charged and discharged, the electrolyte will corrode the stainless steel layer, causing severe corrosion. At the same time, the electrolyte is decomposed in large quantities, resulting in poor battery cycle stability.
[0094] The compound shown in Formula 1 used in the embodiment of the present invention can form a passivation layer on the surface of the stainless steel layer, which can effectively avoid direct contact between the electrolyte and the stainless steel layer, which is beneficial to inhibiting corrosion of the stainless steel layer and preventing the electrolyte from being continuously decomposed, so that the battery has better cycle stability.
[0095] In the embodiment of the present invention, the compound shown in Formula 1 has a strong electronegativity, has a strong binding energy with the stainless steel layer, is adsorbed on the surface of the stainless steel, and promotes the formation of a passivation layer; the compound shown in Formula 1 can form a passivation layer with a network structure on the surface of the stainless steel layer, and the passivation layer has high density, which can effectively avoid direct contact between other components of the electrolyte and the stainless steel layer, which is beneficial to inhibiting the corrosion of the stainless steel layer, and at the same time, the electrolyte is prevented from being continuously decomposed, so that the battery provided by the embodiment of the present invention has good cycle stability; in addition, the passivation layer with a three-dimensional network structure formed by the compound shown in Formula 1 has high stability, which can be suitable for protecting a continuous interface and a stainless steel surface with a large interface.
[0096] In some embodiments, the compound represented by Formula 1 is selected from:
[0097]
[0098] At least one of .
[0099] The compounds represented by Formula 1-1 to Formula 1-10 provided in the embodiments of the present invention are conducive to forming a passivation layer on the stainless steel surface of the battery components, protecting the battery components, avoiding large-scale consumption of the electrolyte, and improving the electrochemical performance of the battery.
[0100] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0101] Example 1
[0102] This embodiment provides a cylindrical lithium battery, and the specific preparation method is as follows:
[0103] (1) Preparation of electrolyte: In an inert atmosphere (water <0.1 ppm, oxygen <1 ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and ethyl acetate (EA) were mixed at a mass ratio of EC:EMC:EA = 30:60:10. After mixing evenly, lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) were added. The mass proportion of LiFSI in the electrolyte was 5wt%, and the mass proportion of LiPF6 in the electrolyte was 9wt%. A certain amount of the compound shown in Formula 1 was then added to obtain an electrolyte.
[0104] (2) Preparation of positive electrode sheets: disperse lithium iron phosphate positive electrode active material, conductive agent acetylene black and binder polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) solvent at a mass ratio of 96:2:2, and stir and mix thoroughly to form a uniform positive electrode slurry; evenly coat the positive electrode slurry on the positive electrode current collector aluminum foil, dry, roll and cut to obtain positive electrode sheets.
[0105] (3) Preparation of negative electrode sheets: Disperse the negative electrode active material graphite, the conductive agent acetylene black, the binder sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in an appropriate amount of deionized water at a mass ratio of 95:2:2:1, and stir and mix thoroughly to form a uniform negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode current collector copper foil, and obtain the negative electrode sheet after drying, rolling and slitting.
[0106] (4) Prepare the diaphragm: 16 μm thick base PE diaphragm.
[0107] (5) Making batteries: The positive electrode sheet, separator and negative electrode sheet are wound to obtain a core, where the separator is between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and the core is placed in a shell (made of nickel-plated stainless steel), and the negative electrode current collector is welded to the shell by laser welding. After drying, the electrolyte is injected. After standing and charging the battery cell to 3.6V at 0.1C at 45°C, the formation (forming a passivation layer) and capacity separation processes are completed to complete the preparation of the battery.
[0108] The type of the compound represented by Formula 1, the addition amount of the compound represented by Formula 1, the preparation parameter conditions and the sample naming are shown in Table 1.
[0109] Comparative Example 1
[0110] This comparative example provides a cylindrical lithium battery, and the specific preparation method is as shown in Example 1, except that: the compound shown in Formula 1 is not added to the electrolyte.
[0111] Comparative Example 2
[0112] This comparative example provides a cylindrical lithium battery, and the specific preparation method is as shown in Example 1, except that: 2.5% of a film-forming additive VC (Vinylene Carbonate) is added to the electrolyte.
[0113] Comparative Example 3
[0114] This comparative example provides a cylindrical lithium battery, and the specific preparation method is as shown in Example 1, except that: 2.5% of a film-forming additive FEC (Fluoroethylene carbonate) is added to the electrolyte.
[0115] Comparative Example 4
[0116] This comparative example provides a cylindrical lithium battery, and the specific preparation method is as shown in Example 1, except that: 2.5% of a film-forming additive VEC (4-Vinyl-1,3-dioxolan-2-one, vinyl ethylene carbonate) is added to the electrolyte.
[0117]
[0118] Performance Test:
[0119] 1. Test method:
[0120] 1. High temperature cycle test: Place the battery at 45°C and use 1.5 C current for charge and discharge cycles. Record the maximum discharge capacity of the first three times as Q, and the capacity after 1000 cycles as Q2. Calculate the capacity retention rate of the battery after high temperature cycling by the following formula: Capacity retention rate (%) = Q2 / Q×100.
[0121] 2. Solder point corrosion: Place the battery at room temperature and use 1.5 C current for 10 charge and discharge cycles. Then disassemble the battery and observe the solder point corrosion.
[0122] 3. Passivation layer element detection method: disassemble the formed battery, cut out the part where the electrolyte contacts the stainless steel layer, and use a scanning electron microscope energy dispersive spectrometer (EDS) for element detection.
[0123] 2. Test Results
[0124] The test results are shown in Table 2.
[0125]
[0126] The test results are shown in Table 2 above. It can be seen from the results listed in the table that, compared with the comparative example, the EDS test results found the presence of sulfur in the contact area between the electrolyte and the stainless steel layer, indicating that the stainless steel layer has a passivation layer and the passivation layer is formed by the reaction of the compound shown in Formula 1. The embodiment has a significant anti-corrosion effect. In addition, the capacity retention rate after high-temperature cycling is significantly improved. At the same time, only the battery including the compound shown in Formula 1 in the electrolyte can prevent stainless steel from being corroded, while conventional additives such as VC, FEC, etc. have no effect. These results show that the battery proposed in the present invention has outstanding advantages.
[0127] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A battery, characterized in that: The battery is a cylindrical battery, comprising an electrolyte and a battery component in contact with the electrolyte; At least the contact surface of the battery component with the electrolyte includes a stainless steel layer; The electrolyte includes a compound shown in Formula 1, and the compound shown in Formula 1 is: wherein m is an integer of 0 to 3, n is an integer of 0 to 3, and m and n are not both 0, p is an integer of 1 to 5, R0 is a single bond or a methylene group, R1 is hydrogen, halogen, a hydrocarbon group having 1 to 5 carbon atoms, or a halogenated hydrocarbon group having 1 to 5 carbon atoms, and R2, R3, and R4 are independently , , , , , or ; The battery includes a cover plate and a negative electrode current collector, and the battery component includes a portion on the cover plate that is welded to the negative electrode current collector, and the portion includes a stainless steel layer; The cross-sectional area of the portion of the cover plate that is welded to the negative electrode current collector is 5 mm 2 ~400 mm 2 The compound represented by Formula 1 forms a passivation layer on the stainless steel layer at the contact surface between the battery component and the electrolyte, and the elements in the passivation layer include sulfur.
2. The battery according to claim 1, characterized in that The compound represented by Formula 1 is selected from: At least one of .
3. The battery according to claim 1, characterized in that In the electrolyte, the mass proportion of the compound represented by Formula 1 is 0.02% to 10%.
4. The battery according to claim 1, characterized in that The battery comprises a shell, and the battery component comprises a portion on the shell that is welded to the negative electrode current collector, and the portion comprises a stainless steel layer.
5. The battery according to claim 4, characterized in that The cross-sectional area of the portion of the shell that is welded to the negative electrode current collector is 5 mm 2 ~400 mm 2 .
6. The battery according to claim 1, characterized in that The outer diameter of the shell of the cylindrical battery is 20 mm to 65 mm.
7. The battery according to any one of claims 1 to 5, characterized in that: The electrolyte satisfies any one of the following (1) to (3): (1) The electrolyte contains a solvent, and the solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether compound solvent, a phosphorus-containing compound solvent, a sulfur-containing compound solvent, and an aromatic fluorine-containing compound solvent; (2) The electrolyte contains a conductive salt, and the conductive salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethylsulfonyl)imide; (3) The electrolyte contains an additive, and the additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate and succinic anhydride.
8. The battery according to any one of claims 1 to 5, characterized in that: The battery also includes a positive electrode active material, which includes lithium iron phosphate, lithium cobalt oxide, and a ternary material LiNi x Co y MnzO2, lithium manganese iron phosphate materials, lithium-rich manganese-based materials xLi2MnO3·(1-x)LiMO2, lithium nickel manganese oxide, lithium manganese oxide, sodium iron phosphate materials, three-dimensional tunnel-type Na 0.44 At least one of MnO2, P2 layered NaMO2, NaFePO4, Na4Fe3(PO4)2P2O7, Na3V2(PO4)3, Na3V2(PO4)2F3, Na2Fe(CN)6 and Na2MnFe(CN)6.
9. The battery according to any one of claims 1 to 5, characterized in that: The battery also includes a negative electrode material including at least one of graphite, hard carbon, a silicon-containing compound, and silicon.
Citation Information
Patent Citations
Battery
CN118281343A
Electrolyte additive, electrolyte and electrochemical device
CN118486898A
Cited By
battery
EP4787603A1
Battery
WO2026056237A1